Organizational Practices of Income-Generating Projects: Basis for IGP Model Development - Fershie D. Yap (Center for Risk Management & Sustainability and RSF Press, 2022)
This research attempted to develop a proposed model for income-generating projects (IGPs) through their organizational practices to ensure their performance as expected. The study determined the level of performance of the IGPs operated; the status of organizational practices in terms of unit/organization structure, internal control, financial management, strategic planning, human resource management, and the marketing mix; the differences between means when grouped according to IGPs categories; and the predictor variables of IGP performance. The descriptive and causal design was assisted by the validated and reliability-tested researcher-made survey questionnaire. Data gathered from the 320 respondents participated by the IGP employees of the 13 State Universities and Colleges in Central Luzon were statistically interpreted using descriptive analysis, one-way analysis of variance, and multinomial logistic regression. The results show that in terms of individual IGPs, the non-agri-based projects are performing well compared with agri-based projects; however, both of them are not performing excellently. The IGPs were not practicing the organizational practices in their operation at all times but occasionally. The test of difference of the organizational practices between IGPs operated shows that formalization, risk assessment, information & communication system, financial reporting & analysis, vision and mission, business plan/planning, motivation, price, and promotion are statistically significant in operating agri-based IGPs; while all of the organizational practices are statistically significant in operating non-agri-based IGPs. Multinomial logistic regression indicated that there was a combination of organizational practices fit in operating agri-based and non-agri-based IGPs to achieve a low, average, and high performance.